Correction: Hegazy et al. Terazosin Interferes with Quorum Sensing and Type Three Secretion System and Diminishes the Bacterial Espionage to Mitigate the Salmonella Typhimurium Pathogenesis. Antibiotics 2022, 11, 465 - Wael A. H. Hegazy; Ibrahim M. Salem; Hadil Faris Alotaibi; El-Sayed Khafagy; Doaa Ibrahim (Antibiotics)
In the original publication, there was a mistake in Figure 2C as published [...]